A Phase I Study of Triapine(®) in Combination with Doxorubicin in Patients with Advanced Solid Tumors - Schelman, William R. (2008)
PURPOSE: To assess the maximum-tolerated dose (MTD), dose-limiting toxicity (DLT), pharmacokinetics and antitumor activity of Triapine(®) administered in combination with doxorubicin. STUDY DESIGN: Patients were treated with doxorubicin intravenously (IV) on day 1 and Triapine(®) IV on days 1-4 of a 21-day cycle. The starting dose (level 1) was doxorubicin 60 mg/m(2) and Triapine(®) 25 mg/m(2). PK analysis was performed at various time-points before and after treatment. RESULTS: Twenty patients received a total of 49 courses of treatment on study. At dose level 2 (doxorubicin 60 mg/m(2), Triapine(®) 45 mg/m(2)), 2 patients experienced DLTs (febrile neutropenia, grade 4 thrombocytopenia). An additional 3 patients were enrolled at dose level 1 without initial toxicity. Enrollment then resumed at dose level 2a with a decreased dose of doxorubicin (45 mg/m(2)) with Triapine(®) 45 mg/m(2). The 2 patients enrolled on this level had 2 DLTs (diarrhea, CVA). Enrollment was planned to resume at dose level 1; however, the sixth patient enrolled to this cohort developed grade 5 heart failure (ejection fraction 20%, pretreatment EF 62%) after the second course. Thus, doxorubicin and Triapine(®) were reduced to 45 mg/m(2) and 25 mg/m(2), respectively (level 1a), prior to resuming enrollment at dose level 1, the MTD. The main drug-related toxicity was myelosuppression. Non-hematologic toxicities included mild-to-moderate fatigue, grade 3 diarrhea and grade 4 CVA. There was one treatment-related death due to heart failure. While no objective responses were observed, subjective evidence of clinical activity was observed in patients with refractory melanoma and prostate cancer. CONCLUSIONS: Pretreated patients with advanced malignancies can tolerate the combination of Triapine(®) and doxorubicin at doses that achieve subjective clinical benefit with the main treatment-related toxicities being myelosuppression and fatigue. The MTD was determined to be doxorubicin 60 mg/m(2) on day 1 and Triapine(®) 25 mg/m(2) on days 1-4 of a 21 day cycle.